Bullous pemphigoid in the first year. Case report and review of the relevant literature. - Scoppio, B.M.; Mazzotta, F.; Garofalo, L.; Coviello, C.; La Forgia, N.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2003)
A case of bullous pemphigoid arisen at the age of four months is reported and the relevant literature reviewed, picking out other 20 cases arisen within the first year. Bullous pemphigoid cannot be differentiated from linear IgA dermatosis and acquired inflammatory epidermolysis bullosa, basing themselves only on clinical features. The differential diagnosis from the latter is difficult even with the common immunofluorescence techniques. Bullous pemphigoid is more rare of dermatitis herpetiformis and linear IgA dermatosis in children. Moreover, it starts more precociously, given that one third of the cases arising in the first 14 years start in the first year and, among those ones arising in the first year, more than two thirds start in the first four months of life. The clinical severity of bullous pemphigoid in children is highly variable, ranging from cases which heal with only topical treatment to cases requiring, as the case here reported, an aggressive immunosuppressive treatment. In fact, the severity of our case, due to the hydroelectrolytic imbalance and to the alteration of inflammation indexes, with platelets more than 1,000,000, led us to administrate high dose -7 mg/kg- cyclosporin.